Sosialisasi Dan Stop ! Perundungan Di Sekolah Menuju Lingkungan Sekolah Bebas Perundungan - Syafwar, Robi; Marwenny, Elwidarifa; Fauzi, Engrina; Wahyuni, Sry; Citra, Helfira; Harniwati, Harniwati; Falillah, Aulia; Puspita, Liza; Putra, Yolan Dwi (Jurnal Pengabdian Masyarakat Dharma Andalas, 2024)
The Faculty of Law at Dharma Andalas University will conduct a community service activity in the form of a legal education campaign focusing on "Stop Bullying" to create a bullying-free school environment. This campaign aims to raise awareness about bullying, which is a repetitive aggressive behavior intended to harm or weaken individuals who are physically or mentally weaker. Bullying can occur physically, verbally, socially, or even online. According to data from the Indonesian Child Protection Commission (KPAI) and the Federation of Indonesian Teachers' Unions (FSGI), bullying cases in schools are on the rise, underscoring the urgency for preventive measures. The campaign will be conducted through lectures using laptops and projectors at several schools in Pesisir Selatan. This program aims to help school communities better understand and take preventive actions against bullying, thereby fostering a safe and conducive learning environment for students.